Pengembangan Model Latihan Lompat Jangkit berbasis Circuit Training untuk Atlet Pemula - I Gede Angga Andika; Moch Asmawi Asmawi (Journal Coaching Education Sports, 2022)
This study aims to develop a design of triple jump to obtain empirical data about the effectiveness of the triple jump based circuit training model for beginner athletes. The research method used in this study is the research and development method of Borg and Gall which consists of ten steps. The subjects of this study were male and female athletes in Klungkung regency specifically for triple jump numbers. This research resulted in 10 final training models that have gone through expert evaluations, trials, and revisions. In testing the effectiveness of the training model by using "test-t". The data of this research are in the form of the pretest and posttest of the experimental and control groups. Triple jump based on circuit training with a significance level of 0.05. The results of the average pretest mean = 59.05 are smaller than the average posttest mean = 73.40 in the count an increase of 14.36. The results of the effectiveness of the triple jump training model based on circuit training between pretest and posttest obtained results t0 = 11,145 greater than tt = 0,000, the hypothesis was rejected. Research conclusion that, the triple jump based on circuit training model for beginner athletes is effectively used to improve the triple jump results for beginner athletes.